Faktor Penentu Pemilihan Calon Suksesor Pada Perusahaan Keluarga PT Tancorp Abadi Nusantara - Valentino Wijaya; Nur Laili Isnawati (Politeknik Kampar, 2023)
Succession in a family company is very important for the continuity of the family business, especially if the founder/incumbent experiences something unwanted. In choosing a successor candidate, there are things that must be considered such as the readiness of the successor candidate and the relationship in the family relationship itself. PT Tancorp Abadi Nusantara has 4 prospective successors who at this time, each prospective successor is still in the process of succession by being deployed directly to each existing company. This makes each successor candidate have their own expertise in each field. In addition, harmonious family relationships in this family have also been fostered since the beginning even since the founder's father was still around. This research further discusses the readiness of prospective successors and relationships in family relationships as determining factors in the selection of prospective successors.